Do medical schools teach medical humanities? Review of curricula in the United States, Canada and the United Kingdom. Issue 1 (8th June 2021) - Howick, Jeremy; Zhao, Lunan; McKaig, Brenna; Rosa, Alessandro; Campaner, Raffaella; Oke, Jason; Ho, Dien
Abstract: Rationale and objectives: Medical humanities are becoming increasingly recognized as positively impacting medical education and medical practice. However, the extent of medical humanities teaching in medical schools is largely unknown. We reviewed medical school curricula in Canada, the UK and the US. We also explored the relationship between medical school ranking and the inclusion of medical humanities in the curricula. Methods: We searched the curriculum websites of all accredited medical schools in Canada, the UK and the US to check which medical humanities topics were taught, and whether they were mandatory or optional. We then noted rankings both by Times Higher Education and U.S. News and World Report and calculated the average rank. We formally explored whether there was an association between average medical school ranking and medical humanities offerings using Spearman's correlation and inverse variance weighting meta‐analysis. Results: We identified 18 accredited medical school programmes in Canada, 41 in the UK, and 154 in the US. Of these, nine (56%) in Canada, 34 (73%) in the UK and 124 (80%) in the US offered at least one medical humanity that was not ethics. The most common medical humanities were medical humanities (unspecified), history, and literature (Canada); sociology and social medicine, medical humanities (unspecified), and art (UK); and medical humanities (unspecified), literature and history (US). Higher ranked medical schools appeared less likely to offer medical humanities. Conclusions: The extent and content of medical humanities offerings at accredited medical schools in Canada, the UK and the US varies, and there appears to be an inverse relationship between medical school quality and medical humanities offerings. Our analysis was limited by the data provided on the Universities' websites. Given the potential for medical humanities to improve medical education and medical practice, opportunities to reduce this variation should be exploited.